Moderate Islam vis-à-vis Salafism: Ideological Competition and Power Struggle in West Nusa Tenggara - Derajat, Anna Zakiah; Syafiqurrahman, Syafiqurrahman (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2025)
Following the collapse of the New Order, the Reformation era encouraged the development of transnational Islamic movements, including the puritanical Salafi-Wahhabi ideology in Lombok, which opposed the Nahdlatul Wathan Islamic tradition, triggering ideological, social, and political tensions. This study analyses the contestation between the two groups through Quintan Wiktorowicz's Islamic Activism approach, focusing on mobilisation strategies, movement framing, and socio-political implications. Two main questions guide the analysis: (1) What mobilisation and framing strategies do Salafi-Wahhabi and NW groups use to build ideological influence in Lombok? (2) What are the implications of this ideological competition for the socio-political dynamics of Muslims in Lombok? This qualitative study uses a literature review and online interviews with religious and community leaders. Findings indicate that Salafi-Wahhabi gained significant support from Saudi Arabian institutions such as Rabithah al-‘Alam al-Islami and the Islamic Development Bank, which contributed to education, the construction of mosques and Islamic boarding schools, and the dissemination of religious literature. This competition reinforces social polarisation and fragmentation, particularly through digital media and the hijrah movement. This conflict disrupts social cohesion and religious practices, necessitating a dialogic approach to ease tensions and maintain harmony in Lombok.